Acanthephyra pelagica ... - D'Acoz, Cédric D'Udekem; Degrave, Sammy (Zenodo, 2018)
Acanthephyra pelagica (Risso, 1816) Cosmopolitan, pelagic, recorded southern limit: 60°S, i.e. south of the Polar Front (Wasmer 1986; Iwasaki & Nemoto 1987a; Wasmer 1993; Tiefenbacher 1994); also recorded between the Campbell and Antipode Islands (Webber et al. 1990), from Crozet Islands (Ledoyer 1979) and Argentinean Patagonia (Boschi 1973; Boschi et al. 1981). Burukovsky & Romensky (1982) restored the name A. sica Spence Bate, 1888 for southern forms of this species, considered to have a more carinate carapace than the northern Atlantic form. This proposal has not gained wider acceptance and until the systematics of the A. pelagica species complex are sorted, the Southern Ocean form is best retained under this name. ... : Published as part of D'Acoz, Cédric D'Udekem & Degrave, Sammy, 2018, A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps, pp. 201-240 in Zootaxa 4392 (2) on page 217, DOI: 10.11646/zootaxa.4392.2.1, http://zenodo.org/record/1195302 ...